Immagini del tempo degli dei, immagini del tempo degli uomini : un'analisi delle iconografie dei mesi nei calendari figurati romani e bizantini e del loro contesto storico-culturale - Parodo, Ciro, (Archaeopress Roman archaeology ;, 2017)
A characteristic shared by the Roman and Byzantine illustrated calendars is that they represent the 12 months of the year, referable to an iconographic repertoire which is divided into three themes: the astrological-astronomical, the festive-ritual and the rural-seasonal. With regard to the first type, the months are depicted through images of the signs of the zodiac, often associated with images of the guardian deities of the months; the second category includes depictions of the months that refer to some important religious festivals; finally, the third theme includes images of the months that allude to the most important work activities performed in the countryside.